Why Has English Become the Language for all the Written Materials at the International Level? (Global Journal of Human-Social Science, 2017)
This paper is an attempt to explain the reasons and the factors that have made the English language the language of most of the written materials around the world
Keywords: writing skills; english as a lingua franca; english as a second language; english as a foreign language; international english; global english; writin